2020
DOI: 10.5435/jaaosglobal-d-20-00138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resident Involvement on Postoperative Complications After Shoulder Arthroscopy: A Propensity-Matched Analysis

Abstract: Purpose: Shoulder arthroscopy is the second most frequently performed procedure by orthopaedic surgeons taking the American Board of Orthopaedic Surgery part II examination. However, the impact of resident involvement on outcomes after shoulder arthroscopy is poorly understood. The aim of this study was to investigate whether resident involvement in shoulder arthroscopic procedures affects postoperative complication rates and surgical time using propensity score-matched cohorts. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…This agrees with previous studies across various divisions of orthopedic surgery, including shoulder, knee, hip, spine, and trauma [ 3 6 , 10 33 ]. Additionally, this study agrees with the well-documented conclusion that resident presence increases operation time [ 3 , 4 , 13 , 15 17 , 21 , 22 , 25 , 29 , 31 , 33 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with previous studies across various divisions of orthopedic surgery, including shoulder, knee, hip, spine, and trauma [ 3 6 , 10 33 ]. Additionally, this study agrees with the well-documented conclusion that resident presence increases operation time [ 3 , 4 , 13 , 15 17 , 21 , 22 , 25 , 29 , 31 , 33 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, and in disagreement with other studies and the present study, Basques et al found no increase in operation time with resident participation [ 18 ]. Also, examining shoulder arthroscopy, Gulbrandsen et al used a propensity-matched analysis to demonstrate that there was no difference in the overall rate of 30-day complications in the resident versus nonresident group ( P =0.576) [ 13 ]. Jovan et al illustrated no significant increase in 30-day postoperative outcomes when examining resident involvement in shoulder stabilization surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 9 The number of studies that did not demonstrate the existence of the effect is still growing, mainly in research on groups of medical specialties. 10 , 11 , 12 , 13 Therefore, the existence and size of this effect still need to be studied, as well as its implications for medical training and patient care in university hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional open surgery has largely been abandoned. Arthroscopic capsular release has the advantages of less trauma, fast postoperative recovery, less pain, and good shoulder joint function recovery (4)(5)(6), which is gradually more commonly applied clinically. However, during shoulder arthroscopy, extensive and complete capsular release is required in order to achieve good results, so tissue damage, pain, edema and bleeding are unavoidable.…”
Section: Introductionmentioning
confidence: 99%